2013
DOI: 10.1371/journal.pone.0075851
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Microarray Immunohistochemical Detection of Brachyury Is Not a Prognostic Indicator in Chordoma

Abstract: Brachyury is a marker for notochord-derived tissues and neoplasms, such as chordoma. However, the prognostic relevance of brachyury expression in chordoma is still unknown. The improvement of tissue microarray technology has provided the opportunity to perform analyses of tumor tissues on a large scale in a uniform and consistent manner. This study was designed with the use of tissue microarray to determine the expression of brachyury. Brachyury expression in chordoma tissues from 78 chordoma patients was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
(34 reference statements)
3
33
1
Order By: Relevance
“…Zhang and associates used a tissue microarray to evaluate the effects of the brachyury expression level on the overall survival rate. Their study found no correlation between the brachyury expression level and clinical situations that indicate a poor prognosis [111].…”
Section: Brachyurymentioning
confidence: 93%
“…Zhang and associates used a tissue microarray to evaluate the effects of the brachyury expression level on the overall survival rate. Their study found no correlation between the brachyury expression level and clinical situations that indicate a poor prognosis [111].…”
Section: Brachyurymentioning
confidence: 93%
“…Representative areas of 100 paraffin-embedded osteosarcoma tumor specimens for each case were selected and prepared as previously described (32). Briefly, three areas of tumor parts per case were selected for assembling the recipient master block to ensure accurate representation of the selected cores.…”
Section: Methodsmentioning
confidence: 99%
“…The material and methods of placenta TMA were provided in our previous study [13]. In this study, placenta TMA was used to detect the expression of HMGB1 and RAGE in patients with severe PE and normal controls.…”
Section: Immunohistochemistry In Placental Tissue Microarraymentioning
confidence: 99%